Effective MySQL optimizing SQL statements - Bradford, Ronald (Oracle press, 2012)
The first book in the new Oracle Press Effective MySQL series from Oracle ACE Director Ronald Bradford and his team of experts takes readers through critical and exacting elements of optimization, offering Bradford's personal insights, tips, and revelations.